Two new species of Cnemidophorus (Squamata: Teiidae) of the C. ocellifer group, from Bahia, Brazil - Arias, Federico José (2011)
Two new species of Cnemidophorus are described from the right bank of the São Francisco river, in the northwestern part of state of Bahia, Brazil. Both species are assigned to the Cnemidophorus ocellifer group and are distinguished from all other congeners on the basis of lepidosis and color pattern. One of them, Cnemidophorus cyanurus, shares with the species of the subgroup of C. littoralis (C. abaetensis, C. littoralis and C. venetacaudus), a bluish green tail, spurs on the heels of males, 6–7 supraciliaries, a high number of femoral pores (27–45), a row of enlarged scales in the dorsal part of the humerus, and 8 to 10 rows of ventral scales. The second species, Cnemidophorus nigrigula, shares with the C. ocellifer subgroup (composed of C. ocellifer, C. mumbuca, C. jalapensis and C. confusionibus) a low number of femoral pores (14– 21), enlarged scales in the temporal region posterior to the third subocular, 5 supraciliaries, 6 to 8 rows of ventral scales, and a brown tail color. It is also characterized by males being conspicuously larger than females and by females retaining the juvenile color pattern, which is lost in adult males. The latter characteristic has not been reported in any species of the C. ocellifer group before now. The two new species occur sympatrically at Santo Inácio.